2012
DOI: 10.1182/blood-2012-05-429977
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution imaging of remodeled synaptic actin reveals different synergies between NK cell receptors and integrins

Abstract: Natural killer (NK) cells secrete lytic granules to directly kill virus-infected or transformed cells and secrete cytokines to communicate with other cells. Threedimensional super-resolved images of F-actin, lytic granules, and IFN-␥ in primary human NK cells stimulated through different activating receptors reveal that both IFN-␥ and lytic granules accumulated in domains where the periodicity of the cortical actin mesh at the synapse opened up to be penetrable. Ligation of some activating receptors alone (eg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 49 publications
4
60
0
Order By: Relevance
“…With increased density of synaptic F-actin, it was possible that degranulation is obstructed in the absence of Coro1A, because lytic granules are secreted through hypodense regions of the F-actin network at the NK cell synapse (12)(13)(14). To determine if Coro1A is required for the formation of granule-permissive openings in actin meshworks, we measured activation-induced clearances in the synaptic F-actin network using STED imaging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With increased density of synaptic F-actin, it was possible that degranulation is obstructed in the absence of Coro1A, because lytic granules are secreted through hypodense regions of the F-actin network at the NK cell synapse (12)(13)(14). To determine if Coro1A is required for the formation of granule-permissive openings in actin meshworks, we measured activation-induced clearances in the synaptic F-actin network using STED imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Although cortical F-actin has long been considered a barrier to exocytosis of granule-like organelles (11) in some cell types, ligation of NK cell activating and adhesion receptors results in the formation of conduits in F-actin that permit and actually facilitate NK cell degranulation (12)(13)(14). This finding suggests that fine regulation and deconstruction of the synaptic F-actin meshwork is required for the formation of granule-permissivesized clearances (12).…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] Superresolution microscopy revealed that activating receptor ligation triggers remodeling of cortical actin in specific domains within the NK-cell immune synapse where lytic granules and vesicles containing IFN-g accumulate. [9][10][11][12][13] Multiple myeloma (MM) is a hematologic malignancy characterized by a clonal proliferation of plasma cells in bone marrow and is associated with progressive dysregulation of the immune system. 14 NK cells may initially contribute to the control of malignant cells [15][16][17] and evidence suggests that NKG2D is involved in NK-cell recognition of MM cells.…”
Section: Introductionmentioning
confidence: 99%
“…2). As mentioned above, LFA-1, which has also been implicated in conjugate formation of NK cells, was not involved in cryptococcal killing (45,46). Although conjugate formation can be achieved by other signaling pathways, the lack of Rac and LFA-1 involvement may suggest an unidentified actin remodeling process (45).…”
Section: Discussionmentioning
confidence: 94%